Critical Success Factors Aspects of the Enterprise Resource Planning Implementation - Nikitović, Milorad; Strahonja, Vjeran (Journal of Information and Organizational Sciences, 2012)
Considering a global importance of small and medium sized enterprises (SMEs) they are in the spotlight of ERP implementation retail stores. Many of the relevant studies indicate the importance and diversity of the ERP implementation process. This paper presents results of the authors' research of the implementation success factors from the point of view of implementation participants. Based on the experience of a number of ERP implementations, authors compare the Croatian and international implementing practice of ERP solutions, taking into account the same critical success and the same ERP solution. Te emphasisis is put specifically on the three key participants in an implementation process: CEOs, project managers and successful-advanced users. Regardless of the relatively limited number of end users who took part in this study, it indicates a significant coincidence of Croatian and international practices in the part of perception of the critical success factors for ERP implementation, but also different views of key participants in the successful implementation.